Логистические центры как фактор устойчивого развития АР Крым - Саломатина, Л.Н. (Економічні інновації, 2013)
Розглянуто основні проблеми створення логістичних центрів в АР Крим, які є найважливішими чинниками сталого розвитку не тільки Кримського напівпострова, але й економічної складової стратегії переходу Українського Причорномор’я до сталого розвитку. The paper covers the main problems converting creation of logistic centers in AR Crimea which are the most important factor of sustainable development not only of Crimea peninsula but of the economic component of transition strategy of the Ukrainian Black Sea to sustainable development.